2000
DOI: 10.1046/j.1365-2141.2000.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐prolymphocytic leukaemia with spontaneous remission

Abstract: T-prolymphocytic leukaemia (T-PLL) is a rare dis-order with a poor prognosis. A 69-year-old man was diagnosed as having a small-cell variant of T-PLL according to the French-American-British classification by haematological, immunological and ultrastructural studies, although the cells had a CD7- phenotype and no chromosomal abnormality. He had no symptoms or organomegaly. The number of his lymphocytes, 53.7 x 109/l at the time of diagnosis, gradually decreased without therapy, and he was in complete remission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The frequency of 14q32 abnormalities on conventional cytogenetic analysis ranged from 25 to 76.6% in cases with T-PLL [1][2][3]. A total of 30 T-PLL cases, including 11 in the present study, have been reported in Japan [21,[26][27][28][29][30][31][32][33][34]; however, the frequency of typical chromosomal abnormalities involving 14q32 and Xq28 is low (3.3%) according to conventional methods. These data confirm a previous report [21].…”
Section: Discussionmentioning
confidence: 61%
“…The frequency of 14q32 abnormalities on conventional cytogenetic analysis ranged from 25 to 76.6% in cases with T-PLL [1][2][3]. A total of 30 T-PLL cases, including 11 in the present study, have been reported in Japan [21,[26][27][28][29][30][31][32][33][34]; however, the frequency of typical chromosomal abnormalities involving 14q32 and Xq28 is low (3.3%) according to conventional methods. These data confirm a previous report [21].…”
Section: Discussionmentioning
confidence: 61%
“…A total of 48% of treated patients for whom response data were available showed an initial response, but all eventually progressed. Surprisingly, the disease in one patient spontaneously regressed and stayed in remission for the period of follow‐up (55 months) . The cause of death was disease progression in 86% of patients who died during the follow‐up period.…”
Section: Systematic Review Of Previous Cases Of T‐pll‐svmentioning
confidence: 98%
“…Some authors have noted atypical features in patients with leukaemia undergoing spontaneous remission. In a report of a patient with T‐prolymphocytic leukaemia, Shichishima et al suggested that absence of a CD7 positive phenotype and lack of structural abnormalities of 14q might have contributed to the patient's subsequent spontaneous complete remission 10 . It is important to note that remission is by no means synonymous with cure; in many cases the remission is short lived 8 and development of second malignancies has been reported with high frequency – 40% in patients with spontaneous remission of chronic lymphocytic leukaemia 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous remission of leukaemia is rare. This phenomenon has been reported in most leukaemias, including chronic myeloid leukaemia, 6 chronic lymphocytic leukaemia, 7 acute myeloid leukaemia, 8 and rarer disorders such as hairy cell leukaemia 9 and T‐prolymphocytic leukaemia 10 . The mechanism is not well understood.…”
Section: Discussionmentioning
confidence: 99%